Optimization of Process Parameters on Fatigue and Compressive Strength of AL7075/Coconut Shell Ash Composite - Gambo, A. V.; Njoku, C. O.; Bello, Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The study investigates the effect of coconut shell ash particulate (CSAp) on the fatigue and compressive strength of Aluminium (Al) 7075 metal matrix composite; and optimized by Taguchi Grey Relational Analysis (GRA). The composites were prepared by conventional double stir casting method with varying coconut shell ash content (5wt%, 10wt%, 15wt% and 20wt%). Five factors, four levels Taguchi experimental design were used to optimize the number of experiments. The factors considered were reinforcement fraction, processing temperature, stirring speed, stirring time and particle size of Al/CSAp reinforcement in the matrix. Taguchi L16 orthogonal array was employed in fabricating different samples of the composite. The significant effect of the experimental design parameters on the responses was investigated using analysis of Variance (ANOVA). The results for the fatigue strength of the Aluminium/CSAp composite showed that processing temperature with a contribution of 57.55% has the highest influence on the fatigue; followed by reinforcement fraction with 11.49%, particle size with 14.25%, stirring speed with 8.93%, and stirring time with 1.11% in addition, the ANOVA for compressive strength of the composite showed that stirring speed with a contribution of 70.38% has the highest influence on the compressive strength; followed by particle size, with 24.22%, processing temperature, with 0.55%, reinforcement fraction, with 0.11%, and stirring time, with 0.06%. The optimal combination for the Taguchi grey relational analysis was coconut shell ash particles at 10wt%, stirring speed at 600rpm, processing temperature at 850oC, stirring time at 120secs, and particle size at 25µm. Stirring speed and processing temperature were considered significant contributors to the change in grey relational grade (GRG) of the composite. Confirmatory experiments carried out using the optimal parameters (CSAp2SS4PT3ST2PS1) showed an improvement in the fatigue and compressive strength of the optimized composite of 36.4% and 30.7% over the initial settings.